Additives for the production of bubble-containing compositions

By combining specific carboxymethylated cellulose nanofibers with nonionic water-soluble polymers and surfactants, the problem of insufficient bubble stability and foaming in the prior art is solved, and higher bubble stability is achieved and foaming properties.

CN116615465BActive Publication Date: 2025-02-25NIPPON PAPER IND CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180079753.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-27
Filing Date
2021-11-25
Publication Date
2025-02-25
Estimated Expiration
2041-11-25

AI Technical Summary

Technical Problem

In the prior art, when using water-soluble carboxymethyl cellulose, the bubble persistence is insufficient, and although chemically modified cellulose nanofibers can improve bubble stability, the bubble property is slightly worse.

Method used

Air bubble-containing compositions are prepared by using carboxymethylated cellulose nanofibers with specific carboxymethyl substitution and cellulose type I crystallinity with nonionic water-soluble polymers and/or surfactants. Additives for manufacturing.

Benefits of technology

The bubble-containing composition is improved to improve the bubble property and bubble stability, so that the resulting bubbles are more stable and the bubble-burning performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116615465B_ABST
    Figure CN116615465B_ABST
Patent Text Reader

Abstract

The present invention provides an additive for producing a bubble-containing composition that can impart high bubble stability and high foaming properties. The additive for producing a bubble-containing composition is prepared by combining carboxymethylated cellulose nanofibers having a carboxymethyl substitution degree of 0.01 to 0.50 per glucose unit and a cellulose I type crystallinity of 40% or more with a nonionic water-soluble polymer and / or a surfactant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an additive for producing a bubble-containing composition, which can promote foaming and improve the stability of generated bubbles by adding the additive during the production of the bubble-containing composition or to the bubble-containing composition. Background Art

[0002] Cellulose materials such as carboxymethyl cellulose have long been used as additives for foods, cosmetics, detergents (solid soaps, kitchen cleaners, shower gels, shampoos, toothpastes, etc.), resins, pesticides, civil engineering, drilling (bubble shields, etc.) that are intended to contain bubbles or to generate bubbles when used. These additives can form fine and soft bubbles, keep the bubbles in a good dispersed state, and improve the stability of the bubbles.

[0003] For example, Patent Document 1 discloses the use of sodium carboxymethyl cellulose having an etherification degree of 0.8 to 2.0 and a 2% aqueous solution viscosity of 1 to 30 mPa·s as a stabilizer for ice cream with a low air content. Patent Document 2 also discloses the improvement of the bubble stability of egg processed foods by adding a cellulose dry composition containing crystalline fibrous cellulose and / or 30 to 95% by mass of the fibrous cellulose and 5 to 70% by mass of a water-soluble polymer and / or a hydrophilic substance to liquid eggs.

[0004] In addition, Patent Document 3 describes the use of chemically modified cellulose nanofibers as an additive for a bubble-containing composition.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2005-143321

[0008] Patent Document 2: Japanese Patent Application Publication No. 2009-065836

[0009] Patent Document 3: Japanese Patent Application Publication No. 2017-66283 Summary of the invention

[0010] In the methods of Patent Document 1 using water-soluble carboxymethyl cellulose and Patent Document 2 using fibrous cellulose that has not been chemically modified, the persistence of bubbles (bubble stability) is insufficient. In contrast, in the method using chemically modified cellulose nanofibers described in Patent Document 3, a bubble stabilization effect is obtained. However, this time it was found that when only chemically modified cellulose nanofibers are used as an additive, the foaming property (the ability to initially form bubbles) is slightly poor. The present invention further improves the method described in Patent Document 3, and its purpose is to provide an additive for the manufacture of a bubble-containing composition that can maintain bubble stability and has high foaming property (ability to form bubbles).

[0011] With regard to the above-mentioned problems, the inventors have conducted intensive research and found that by using carboxymethylated cellulose nanofibers having a specific degree of carboxymethyl substitution and cellulose type I crystallinity together with a nonionic water-soluble polymer and / or a surfactant to prepare an additive for the production of a bubble-containing composition, the bubble stability of the composition can be maintained and the foaming property can be improved. The present invention is not limited to these and includes the following configurations.

[0012] [1] An additive for producing a bubble-containing composition, comprising carboxymethylated cellulose nanofibers having a carboxymethyl substitution degree of 0.01 to 0.50 per glucose unit and a cellulose I crystallinity of 40% or more, and a nonionic water-soluble polymer and / or a surfactant.

[0013] [2] The additive for producing the bubble-containing composition according to [1], comprising at least a nonionic water-soluble polymer, wherein the nonionic water-soluble polymer is at least one selected from hydroxyethyl cellulose, methyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose or hydroxyethyl methyl cellulose.

[0014] [3] The additive for producing the bubble-containing composition according to [1] contains at least a nonionic water-soluble polymer, wherein the nonionic water-soluble polymer is at least one selected from polyethylene glycol, polyvinyl pyrrolidone, a copolymer of vinyl pyrrolidone and vinyl acetate, galactan, pullulan, mannan, sclerotium gum or guar gum.

[0015] [4] The additive for producing a bubble-containing composition according to any one of [1] to [3], comprising at least a surfactant, wherein the surfactant is at least one selected from the group consisting of sodium lauryl sulfate, lauroyl hydroxysulfobetaine, decyl dimethylamine oxide, lauramine oxide, sodium oleate, sodium laureth sulfate, sodium cocoyl methyl taurate, sodium cocoyl glutamate, potassium laurate, cocoamidopropyl betaine, coconut diethanolamide, lauroamidopropyl betaine, hydrogenated lecithin, and sodium cocoamphoacetate.

[0016] [5] An additive for producing a bubble-containing composition according to any one of [1] to [4], wherein the amount of the nonionic water-soluble polymer and / or surfactant (when both the nonionic water-soluble polymer and the surfactant are contained, the total amount of the two) is 1 to 5000 parts by mass per 100 parts by mass of the carboxymethylated cellulose nanofibers.

[0017] [6] A method for producing a bubble-containing composition, comprising mixing the additive for producing a bubble-containing composition according to any one of [1] to [5] into a material for a bubble-containing composition and stirring the material to foam the material.

[0018] [7] A method for stabilizing bubbles in a bubble-containing composition, comprising adding the additive for producing a bubble-containing composition according to any one of [1] to [5] to the bubble-containing composition.

[0019] By adding the additive of the present invention when manufacturing a bubble-containing composition, the foaming property of the composition can be improved, and the persistence of the bubbles formed (bubble stability) can also be improved. In addition, by adding to a bubble-containing composition, foaming can be further promoted, and bubble stability can be imparted. That is, the additive of the present invention can impart both foaming property and bubble stability to the bubble-containing composition. The additive for manufacturing a bubble-containing composition of the present invention contains specific carboxymethylated cellulose nanofibers and a nonionic water-soluble polymer and / or a surfactant. For example, when an anionic water-soluble polymer is used instead of a nonionic water-soluble polymer, the above-mentioned effect cannot be obtained as shown in Comparative Examples 1 to 3.

[0020] The additive for producing the bubble-containing composition of the present invention can be applied to, for example, food and beverages that are intended to contain bubbles or to generate bubbles when used (dough for ice cream, cakes and muffins, bread, fresh cream, etc.), cosmetics (facial cleansers, shaving creams, etc.), cleaning agents (solid soaps, kitchen cleaners, shower gels, shampoos, toothpastes, etc.), resins, pesticides, civil engineering, drilling (bubble shields, etc.), etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 These are photographs showing the results of Example 1.

[0022] Figure 2 These are photographs showing the results of Example 2.

[0023] Figure 3 These are photographs showing the results of Comparative Example 1.

[0024] Figure 4 These are photographs showing the results of Comparative Example 2.

[0025] Figure 5 These are photographs showing the results of Comparative Example 3.

[0026] Figure 6 These are photographs showing the results of Example 3.

[0027] Figure 7 These are photographs showing the results of Example 4.

[0028] Figure 8 These are photographs showing the results of Example 5.

[0029] Fig. 9 These are photographs showing the results of Example 6.

[0030] Fig.10 These are photographs showing the results of Example 7.

[0031] Fig.11 These are photographs showing the results of Example 8. DETAILED DESCRIPTION

[0032] <Carboxymethylated cellulose nanofiber>

[0033] In the present invention, carboxymethylated cellulose nanofibers (hereinafter, "carboxymethylation" is sometimes abbreviated as "CMization", and cellulose nanofibers are abbreviated as "CNFs.") are obtained by refining carboxymethylated cellulose (CMized cellulose) to a fiber width of the nanometer level, and are generally fine fibers with a fiber width of about 3 to several hundred nm, for example, about 4 to 500 nm. The aspect ratio is not limited, for example, it is 50 or more, preferably 100 or more. The average fiber diameter and average fiber length of CMized CNF can be obtained by calculating the average fiber diameter and fiber length obtained by observing 200 randomly selected fibers using an atomic force microscope (AFM), a transmission electron microscope (TEM) or a field emission scanning electron microscope (FE-SEM). In addition, the aspect ratio can be calculated by dividing the average fiber length by the average fiber diameter. CMized CNF can be obtained by applying mechanical force to CMized cellulose to make it refining (defibration).

[0034] CM cellulose has a structure in which a part of the hydroxyl groups in the glucose residue constituting cellulose is bonded to the carboxymethyl group via an ether bond. CM cellulose sometimes takes the form of a salt, and when CM cellulose is mentioned in this specification, the salt of CM cellulose is also included. Examples of the salt of CM cellulose include metal salts such as sodium salt of CM cellulose.

[0035] <Cellulose raw materials>

[0036] As cellulose raw materials for producing CM-type cellulose, which is a raw material for CM-type CNF, for example, plant materials (e.g., wood, bamboo, hemp, jute, kenaf, farm waste, cloth, pulp (coniferous unbleached kraft pulp (NUKP), coniferous bleached kraft pulp (NBKP), broadleaf unbleached kraft pulp (LUKP), broadleaf bleached kraft pulp (LBKP), coniferous unbleached sulfite pulp (NUSP), coniferous bleached sulfite pulp (NBSP) thermomechanical pulp (TMP), recycled pulp, waste paper, etc.)), animal materials (e.g., ascidian), algae, microorganisms (e.g., acetic acid bacteria (acetobacter)), and materials derived from microbial products, etc., all of which can be used. Cellulose fibers derived from plants or microorganisms are preferred, and cellulose fibers derived from plants are more preferred.

[0037] <CM of cellulose raw materials>

[0038] The CM-modified cellulose used as the raw material of CM-modified CNF can be obtained by carboxymethylating the above-mentioned cellulose raw material by a known method, or a commercially available product can be used. In either case, the CM-modified cellulose having a carboxymethyl substitution degree of 0.01 to 0.50 per anhydrous glucose unit of the cellulose is preferred. As an example of a method for producing such CM-modified cellulose, the following method can be cited.

[0039] Cellulose raw material and 3 to 20 times the mass of water and / or lower alcohol as solvent are used alone or as a mixed medium of two or more. Specifically, as the solvent, there are water, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, etc. As a mercerizing agent, 0.5 to 20 times the mole of alkali metal hydroxide is used relative to the anhydrous glucose residue of the cellulose raw material, specifically sodium hydroxide and potassium hydroxide. The cellulose raw material, the solvent and the mercerizing agent are mixed, and a mercerization treatment is performed at a reaction temperature of 0 to 70°C, preferably 10 to 60°C and a reaction time of 15 minutes to 8 hours, preferably 30 minutes to 7 hours. Thereafter, 0.05 to 10.0 times the mole of the CM agent is added relative to the glucose residue, and an etherification reaction is performed at a reaction temperature of 30 to 90°C, preferably 40 to 80°C and a reaction time of 30 minutes to 10 hours, preferably 1 hour to 4 hours.

[0040] The CM cellulose that is the raw material of CM CNF can maintain at least a part of its fibrous shape even when dispersed in water, which is different from the carboxymethyl cellulose described later as a water-soluble polymer. When the aqueous dispersion of "carboxymethyl cellulose (CM cellulose)" is observed with an electron microscope, a fibrous substance can be observed. On the other hand, even when the aqueous dispersion of carboxymethyl cellulose, which is a water-soluble polymer, is observed, no fibrous substance can be observed. In addition, when "carboxymethyl cellulose" is measured by X-ray diffraction, the peak of cellulose type I crystals can be observed, but cellulose type I crystals are not seen in the carboxymethyl cellulose of the water-soluble polymer.

[0041] <Defibration of CM cellulose>

[0042] CM-modified CNF can be produced by defibration of CM-modified cellulose. The device used for defibration is not particularly limited, and high-speed rotary, colloid mill, high-pressure, roller mill, ultrasonic and other devices can be used. It is preferred to apply a strong shear force to the dispersion of CM-modified cellulose during defibration. In particular, efficient defibration preferably uses a wet high-pressure or ultra-high-pressure homogenizer that can apply a pressure of more than 50MPa and a strong shear force to the above-mentioned dispersion. The above-mentioned pressure is more preferably more than 100MPa, and further preferably more than 140MPa. In addition, before defibration and dispersion treatment with a high-pressure homogenizer, the above-mentioned dispersion can be pre-treated using a known mixing, stirring, emulsifying, and dispersing device such as a high-speed shear mixer as needed.

[0043] From the viewpoint of processing efficiency, the solid content concentration of the dispersion of CM cellulose for fibrillation is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and particularly preferably 0.3% by mass or more. In addition, from the viewpoint of fluidity, it is preferably 10% by mass or less, and more preferably 6% by mass or less.

[0044] <Degree of carboxymethyl substitution>

[0045] In CM-modified CNF, the carboxymethyl substitution degree of each anhydrous glucose unit of cellulose is 0.01 to 0.50. If the carboxymethyl substitution degree is less than 0.01, sufficient bubble stability and foaming properties cannot be obtained. In addition, if the carboxymethyl substitution degree exceeds 0.50, dissolution into the aqueous medium is likely to occur, the fiber form cannot be maintained, and the bubble stability decreases. The lower limit of the carboxymethyl substitution degree is more preferably above 0.10, and further preferably above 0.20. The upper limit of the carboxymethyl substitution degree is more preferably below 0.40. The carboxymethyl substitution degree of CM-modified CNF can be adjusted by controlling the amount of carboxymethylating agent added when the CM-modified cellulose used as the raw material is manufactured, the amount of mercerizing agent, the composition ratio of water to the organic solvent, etc. The carboxymethyl substitution degree of CM-modified cellulose is usually the same as the carboxymethyl substitution degree of CM-modified CNF obtained by defibrating it.

[0046] In this specification, anhydrous glucose unit refers to each anhydrous glucose (glucose residue) constituting cellulose. In addition, the carboxymethyl substitution degree (also referred to as etherification degree) represents the ratio of hydroxyl groups substituted by carboxymethyl ether groups in the hydroxyl groups in the glucose residues constituting cellulose (the number of carboxymethyl ether groups per glucose residue). It should be noted that the carboxymethyl substitution degree is sometimes abbreviated as DS.

[0047] The method for determining the degree of carboxymethyl substitution is as follows:

[0048] Accurately weigh about 2.0g of the sample and put it into a 300mL Erlenmeyer flask with a stopper. Add 100mL of methanol nitric acid (a solution obtained by adding 100mL of extra-grade concentrated nitric acid to 1000mL of methanol) and shake for 3 hours to convert the salt of CMC into H-CMC (hydrogenated CMC). Accurately weigh 1.5-2.0g of the absolutely dry H-CMC and put it into a 300mL Erlenmeyer flask with a stopper. Moisten the H-CMC with 15mL of 80% methanol, add 100mL of 0.1N-NaOH, and shake at room temperature for 3 hours. Using phenolphthalein as an indicator, back-titrate the excess NaOH with 0.1N-H2SO4, and calculate the degree of carboxymethyl substitution (DS value) according to the following formula.

[0049] A=[(100×F'-0.1N-H2SO4(mL)×F)×0.1] / (absolute dry mass of H-CMC(g))

[0050] Carboxymethyl substitution degree = 0.162×A / (1-0.058×A)

[0051] F': Factor of 0.1N-H2SO4

[0052] F: Factor of 0.1N-NaOH.

[0053] <Crystallinity of Cellulose Type I>

[0054] From the viewpoint of improving foamability and bubble stability, the crystallinity of cellulose type I in CMized CNF is 40% or more, preferably 50% or more, and more preferably 60% or more. The crystallinity of cellulose type I in CMized CNF can be controlled by the concentration of the mercerizing agent during the manufacture of the CMized cellulose used as the raw material, the temperature during the treatment, and the degree of CMization. Since a high concentration of alkali is used in mercerization and CMization, type I crystals of cellulose are easily converted into type II, but the degree of modification can be adjusted by adjusting the amount of alkali (mercerizing agent) used, for example, to maintain the desired crystallinity. The upper limit of the crystallinity of cellulose type I is not particularly limited. It is believed that 90% is the upper limit in reality. The crystallinity of cellulose type I of CMized cellulose is generally the same as the crystallinity of cellulose type I of CMized CNF obtained by defibration.

[0055] The method for determining the crystallinity of cellulose type I is as follows:

[0056] The sample was placed in a glass cuvette and measured using an X-ray diffraction measuring device (LabX XRD-6000, manufactured by Shimadzu Corporation). The crystallinity was calculated using the method of Segal et al., using the diffraction intensity of 2θ = 10° to 30° of the X-ray diffraction pattern as the baseline, and the diffraction intensity of the 002 plane at 2θ = 22.6° and the diffraction intensity of the amorphous part at 2θ = 18.5° were calculated according to the following formula:

[0057] Xc=(I002c-Ia) / I002c×100

[0058] Xc = Crystallinity of cellulose type I (%)

[0059] I002c: 2θ = 22.6°, diffraction intensity of 002 surface

[0060] Ia: 2θ=18.5°, diffraction intensity of the amorphous part.

[0061] <Nonionic water-soluble polymer and / or surfactant>

[0062] The additive for manufacturing the bubble-containing composition of the present invention is prepared by mixing the above-mentioned CM-type CNF with a nonionic water-soluble polymer and / or a surfactant. The additive of the present invention may contain both a nonionic water-soluble polymer and a surfactant, or may contain either one. For example, as a nonionic water-soluble polymer, nonionic water-soluble polymers from cellulose such as hydroxyethyl cellulose, methyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl methyl cellulose may be cited, but are not limited to these. In addition, nonionic water-soluble polymers such as polyethylene glycol, polyvinyl pyrrolidone, copolymers of vinyl pyrrolidone and vinyl acetate, galactans, pullulan, mannan, sclerotium gum, and guar gum may be used. Nonionic water-soluble polymers may be used by mixing multiple of the above-mentioned substances, or may be used alone. Among these, hydroxyethyl cellulose, methyl cellulose or polyethylene glycol is preferred. In addition, as surfactants, for example, sodium lauryl sulfate, lauramide propyl hydroxysulfobetaine, decyl dimethylamine oxide, lauramine oxide, sodium oleate, sodium laureth sulfate, sodium cocoyl methyl taurate, sodium cocoyl glutamate, potassium laurate, cocoamidopropyl betaine, coconut oil diethanolamide, lauramide propyl betaine, hydrogenated lecithin, sodium cocoyl amphiacetate, but not limited to these, among which sodium lauryl sulfate, lauramide propyl hydroxysulfobetaine, decyl dimethylamine oxide, lauramine oxide and sodium oleate are preferred, and sodium lauryl sulfate, lauramide propyl hydroxysulfobetaine and decyl dimethylamine oxide are further preferred. Surfactants, for example, can be used by mixing multiple of the above substances, or can be used alone. The specific types of nonionic water-soluble polymers and surfactants can be appropriately selected according to the bubble-containing composition to be manufactured.

[0063] Regarding the mixing ratio of CMized CNF and nonionic water-soluble polymers and / or surfactants, when the amount of CMized CNF is set to 100 parts by mass, the amount of nonionic water-soluble polymers and / or surfactants is preferably 1 to 5000 parts by mass. More preferably, it is 5 to 5000 parts by mass, further preferably 5 to 2000 parts by mass, further preferably 5 to 1000 parts by mass, further preferably 10 to 1000 parts by mass, further preferably 20 to 1000 parts by mass, further preferably 20 to 500 parts by mass. For the "amount of nonionic water-soluble polymers and / or surfactants", when any one of nonionic water-soluble polymers or surfactants is used, it refers to the amount of any one used, and when both nonionic water-soluble polymers and surfactants are used, it refers to the total amount of the two. In addition, the amounts of CMized CNF, nonionic water-soluble polymers, and surfactants are all solid components.

[0064] The method of mixing CM-modified CNF with nonionic water-soluble polymer and / or surfactant is not particularly limited. Dispersions prepared by dispersing both in a dispersion medium such as water may be mixed with each other, or a powder or solid of one dispersion may be added to the other dispersion and mixed.

[0065] <Additives for producing bubble-containing compositions>

[0066] As described above, by mixing CM-CNF having a specific degree of carboxymethyl substitution and cellulose I type crystallinity with a nonionic water-soluble polymer and / or a surfactant, an additive for preparing a bubble-containing composition is prepared. "Bubble-containing composition" refers to a substance containing a gas such as air in a bubble state in a composition. The bubble-containing composition is usually formed by stirring a liquid using a blender or a foamer. For example, as a bubble-containing composition, there can be cited food and beverages that are intended to contain bubbles or foam when used (dough for ice cream, cakes and muffins, bread, whipped cream, etc.), cosmetics (facial cleansers, shaving creams, etc.), cleaning agents (solid soaps, kitchen cleaners, shower gels, shampoos, toothpastes, etc.), resins, pesticides, civil engineering, drilling (bubble shields, etc.), etc., but are not limited to these.

[0067] The "additive for producing a bubble-containing composition" includes additives to be mixed with the bubble-containing composition material (components of the composition before bubbles are contained) when producing the bubble-containing composition and additives added to the bubble-containing composition. In the former case, the bubble-containing composition is formed by foaming the bubble-containing composition material by stirring after the addition of the additive. In the latter case, the additive is uniformly mixed into the composition by stirring after the addition of the additive. In either case, foaming properties (ability to form bubbles) and bubble stability (ability to maintain formed bubbles) can be imparted to the composition.

[0068] When the additive for producing the bubble-containing composition is added to the material for the bubble-containing composition (the components of the composition before containing bubbles), the material for the bubble-containing composition may contain all the components contained in the final bubble-containing composition, or may be a part of the components contained in the final bubble-containing composition. In the latter case, after adding the additive of the present invention, the remaining components of the composition may be mixed after or while the material for the bubble-containing composition (a part of the components of the bubble-containing composition) is foamed. In addition, the material for the bubble-containing composition to which the additive of the present invention is added may contain a component equivalent to a bubble agent for promoting the formation of bubbles and preventing the formed bubbles from merging with each other or disappearing. As the bubble agent, in addition to surfactants such as higher alcohol sulfate ester salts, alkyl ether sulfate ester salts, N-acyl glutamic acid salts, phosphate ester salts, etc., proteins such as collagen and keratin, and cellulose compounds such as carboxymethyl cellulose and crystalline cellulose can also be exemplified.

[0069] The form of the additive for manufacturing the bubble-containing composition is not particularly limited. For example, it may be in the form of a dispersion containing CMized CNF and a nonionic water-soluble polymer and / or a surfactant and using water or the like as a dispersion medium, it may be in the form of a dry solid substance obtained by drying such a dispersion, or it may be in the form of a powder obtained by crushing the dry solid substance. In addition, it may be in the form of a wet solid substance, which is an intermediate state between the dispersion and the dry solid substance. It should be noted that in this specification, a dry solid substance refers to a substance in which the dispersion is deliquated and dried until the amount of liquid such as water becomes less than 12% by mass. The amount of liquid in the dry solid substance can be measured by the following method:

[0070] The dried solid matter was dried in an oven at 105° C. for 12 hours, and the amount of liquid in the dried solid matter was calculated from the mass before and after drying.

[0071] The amount of liquid in the dried solid material (mass %)={1−(mass after drying / mass before drying)}×100.

[0072] When the bubble-containing composition is manufactured with an additive in the form of a dispersion, from the dispersibility of CM-based CNF, the dispersion medium is preferably water or a mixed solvent of water and a hydrophilic organic solvent. The dispersion medium during the manufacture of CM-based CNF can be directly used, or a hydrophilic organic solvent can be added or a part of the dispersion medium can be replaced with a hydrophilic organic solvent to prepare a dispersion medium containing a hydrophilic organic solvent. When using a material containing both water and a hydrophilic organic solvent as a dispersion medium, relative to the total amount of water and the hydrophilic organic solvent, the amount of the hydrophilic organic solvent is preferably more than 10% by mass, more preferably more than 20% by mass, and further preferably more than 25% by mass. The upper limit of the amount is not limited, preferably less than 95% by mass, more preferably less than 80% by mass.

[0073] The hydrophilic organic solvent refers to an organic solvent that is soluble in water. Examples thereof include methanol, ethanol, 2-propanol, butanol, glycerol, butanediol, propylene glycol, acetone, methyl ethyl ketone, 1,4-diol, Alkane, N-methyl-2-pyrrolidone, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, acetonitrile and combinations thereof, but not limited thereto. Among them, lower alcohols having 1 to 4 carbon atoms such as methanol, ethanol and 2-propanol, and polyols such as glycerol, butanediol and propylene glycol are preferred. In view of safety and availability, methanol, ethanol, glycerol, butanediol and propylene glycol are preferred.

[0074] When the additive for producing the bubble-containing composition is in the form of a dry solid substance, it is preferred to adjust the pH of the dispersion of the CMized CNF and the nonionic water-soluble polymer and / or surfactant to 9 to 11 before dehydration and drying. If the pH is adjusted to 9 to 11 before drying, the dispersibility in the bubble-containing composition material or the bubble-containing composition becomes good. When adjusting the pH, an alkali such as sodium hydroxide can be used.

[0075] As the deliquoring and drying method of the dispersion, known methods can be used, for example, spray drying, squeezing, air drying, hot air drying and vacuum drying can be cited. The drying device is not particularly limited, and a continuous tunnel drying device, a belt drying device, a vertical drying device, a vertical turbine drying device, a multi-layer disk drying device, a ventilation drying device, a rotary drying device, an airflow drying device, a spray dryer drying device, a spray drying device, a drum drying device, a drum drying device, a belt drying device, a screw conveyor drying device, a rotary drying device with a heating tube, a vibration conveying drying device, an intermittent box drying device, a ventilation drying device, a vacuum box drying device and a stirring drying device can be used alone or in combination of two or more.

[0076] Among these, in order to be able to evenly supply heat energy directly to the dried object and perform the drying treatment more efficiently in a short time, it is preferable to use an apparatus that forms a thin film for drying from the viewpoint of energy efficiency. In addition, an apparatus that forms a thin film for drying is also preferable from the viewpoint that the dried object can be directly recovered by a simple means such as scraping off the thin film, and an apparatus that forms a thin film for drying is also preferable from the viewpoint of improving the dispersibility of the obtained dry solid substance in the material for the bubble-containing composition or the bubble-containing composition. As an apparatus that forms a thin film for drying, for example, a drum-type drying apparatus and a belt-type drying apparatus that form a thin film on a drum or a belt and dry it can be cited. Among them, a drum-type drying apparatus is preferable because it is easy to dry continuously and to recover the dried object.

[0077] The drum drying device refers to a device that continuously supplies a dispersion to the drum surface while rotating a heated drum, evaporating and concentrating the dispersion medium while adhering the dispersion to the drum surface in a thin film for drying, and scraping the dried material formed on the drum surface with a knife to produce a dry solid material. The drum drying device has a double-drum or two-drum device using two drums or a single-drum device using one drum, and both can be used. Among these, a double-drum device that can adjust the film thickness of the film by adjusting the gap between the drums is preferred.

[0078] The thickness of the dried film is preferably 50 to 1000 μm, more preferably 100 to 300 μm. If it is 50 μm or more, it is easy to scrape after drying, and if it is 1000 μm or less, the dispersibility in the bubble-containing composition material or the bubble-containing composition is improved.

[0079] The drying temperature is not particularly limited. For example, the drying can be performed at a temperature of about 200° C. or less. When drying is performed using a drum drying device or a belt drying device that forms a thin film, the drying temperature refers to the temperature of the drum or belt surface.

[0080] Drying can be performed under normal pressure, vacuum or reduced pressure. Among them, drying under vacuum or reduced pressure can reduce the boiling point of water and increase the evaporation rate, thereby accelerating the drying of the object and reducing the thermal effect on the sample, so it is preferred.

[0081] When drying is performed under vacuum or reduced pressure (hereinafter also referred to as "vacuum drying"), it is preferably performed in the range of 0 to 50 kPa. Low pressure can achieve the advantage of evaporating water at a lower temperature, and is preferably 50 kPa or less, more preferably 30 kPa or less, and further preferably 10 kPa or less.

[0082] During drying, the dispersion is preferably vacuum dried at a relatively low temperature of 40 to 100° C. to obtain a dry solid material. If the drying temperature is low, the production efficiency decreases, so the drying temperature is preferably 40° C. or higher, more preferably 45° C. or higher, and further preferably 50° C. or higher. If the drying temperature is high, cellulose is colored or damaged, so it is preferably 100° C. or lower, more preferably 90° C. or lower, more preferably 85° C. or lower, further preferably 80° C. or lower, and may be lower than 80° C.

[0083] The vacuum drying device is not particularly limited, and a vacuum box drying device, a vacuum drum dryer, a vacuum spray dryer, a vacuum belt dryer, etc. may be used alone or in combination of two or more. A vacuum drum dryer is a device that pre-arranges a heated drum under vacuum or reduced pressure, continuously supplies a dispersion to the drum surface while rotating the drum, evaporating and concentrating the dispersion medium while adhering the dispersion to the drum surface in a thin film for drying, and scrapes the dried material formed on the drum surface with a knife to produce a dry solid substance.

[0084] When the obtained dry solid material is crushed to form a powder, the median particle size of the powder is preferably about 10.0 to 150.0 μm, more preferably 25.0 to 100.0 μm, and further preferably 35.0 to 70.0 μm. If the median particle size is greater than 10.0 μm, it is not easy to cause problems such as powder scattering. If it is less than 150.0 μm, it becomes an appropriate volume, so the packaging operation of the powder becomes easy, which is preferred. The median particle size of the powder can be adjusted by adjusting the conditions of crushing and classification. It should be noted that the median particle size can be measured according to the following steps:

[0085] A sample was prepared using methanol as a dispersion medium so that the scattering intensity was 0.1 to 20%, and the particle size distribution was measured using a laser diffraction particle size analyzer (Mastersizer (registered trademark) 3000 manufactured by Malvern).

[0086] <Addition to the material for bubble-containing composition or bubble-containing composition>

[0087] The bubble-containing composition can be produced by mixing the additive for producing the bubble-containing composition of the present invention into the material for the bubble-containing composition (the components of the composition before containing bubbles) and stirring to foam it. The additive of the present invention can impart good foaming properties to the material for the bubble-containing composition, and can also improve the persistence of the bubbles formed (bubble stability). The material for the bubble-containing composition can contain all the components contained in the final bubble-containing composition, or it can be a part of the components contained in the final bubble-containing composition. In the latter case, after adding the additive of the present invention, the remaining components of the composition can be mixed after the material for the bubble-containing composition (a part of the components of the bubble-containing composition) is foamed or while foaming.

[0088] Furthermore, by adding the additive for producing a bubble-containing composition of the present invention to the bubble-containing composition, foaming can be further promoted and bubble stability can be improved.

[0089] After the additive of the present invention is added to the material for bubble-containing composition or the bubble-containing composition, it is preferably stirred using a known mixing and stirring device to promote foaming. The stirring conditions at this time can be appropriately determined according to the type of bubble-containing composition and the desired degree of foaming, and are not particularly limited. For example, stirring is performed at about 100 to 15,000 rpm, preferably about 500 to 10,000 rpm, for about 1 to 30 minutes, preferably about 1 to 15 minutes.

[0090] The content of the additive of the present invention in the final bubble-containing composition can be appropriately changed according to the type of the bubble-containing composition and the desired degree of foaming, and is not particularly limited. For example, it is preferably added so that the amount of CM-CNF derived from the additive becomes 0.05% by mass or more, and more preferably added so that it becomes 0.1% by mass or more, relative to the amount of the bubble-containing composition.

[0091] Example

[0092] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these.

[0093] <Manufacturing of CM CNF>

[0094] In a double-shaft kneader adjusted to a rotation speed of 100 rpm, 620 parts of isopropyl alcohol (IPA) and a substance obtained by dissolving 10 parts of sodium hydroxide in 30 parts of water were added, and 100 parts of hardwood pulp (LBKP, manufactured by Nippon Paper Industries, Ltd.) with a dry mass of 60 minutes at 100°C were added. Mixing was carried out at 30°C for 90 minutes to prepare mercerized cellulose. Further, 15 parts of IPA and 12 parts of monochloroacetic acid were added while stirring, and after stirring for 30 minutes, the temperature was raised to 70°C for 90 minutes of CM reaction. After the reaction was completed, it was neutralized with acetic acid to pH 7, washed with aqueous methanol, deliquated, dried, and crushed to obtain CM cellulose with a carboxymethyl substitution degree of 0.18.

[0095] The CM-modified cellulose obtained in the above process was adjusted to 1.0% by mass with water and treated three times with an ultra-high pressure homogenizer (20°C, 150 MPa) to obtain a CM-modified CNF dispersion. The average fiber diameter of the obtained fiber was 5 nm, the aspect ratio was 150, and the crystallinity of cellulose type I was 72%.

[0096] <Example 1>

[0097] A 1.0% by mass aqueous dispersion of the CMized CNF obtained above was prepared. In addition, as a nonionic water-soluble polymer, hydroxyethyl cellulose (manufactured by Daicel, trade name SE550) (hereinafter, "hydroxyethyl cellulose" is abbreviated as "HEC") was selected, and a 2.0% by mass aqueous dispersion of HEC was prepared in a manner to obtain a viscosity equivalent to that of the 1.0% by mass aqueous dispersion of CMized CNF. In a 250 ml polypropylene container with a lid (manufactured by AS ONE, trade name: Pack Clean), the obtained 1.0% by mass aqueous dispersion of CMized CNF was mixed with a 2.0% by mass aqueous dispersion of HEC in a manner to obtain a mass ratio as described in Table 1. Each sample was stirred at 3000 rpm for 10 minutes using a homodisper. In order to evaluate the foamability and bubble stability, the height from the bottom surface of the container to the upper surface of the dispersion was measured for both just after stirring and after standing at room temperature for 1 day. In addition, photographs were taken. The photographs are shown in Figure 1 .

[0098] [Table 1]

[0099]

[0100] according to Figure 1 From the photos, it can be seen that in the case of HEC alone, foaming can be confirmed just after stirring, but the bubbles formed almost disappear after standing for 1 day. On the other hand, it can be seen that in the case of CM-CNF alone, the foaming property just after stirring is low. In contrast, it can be seen that the foaming property and bubble stability of the sample formed by mixing HEC and CM-CNF are improved.

[0101] In addition, for the sample in which the above-mentioned CM-modified CNF 1.0 mass % aqueous dispersion and HEC 2.0 mass % aqueous dispersion were mixed in a mass ratio of 90:10 to 30:70 (i.e., HEC was in the range of 22 to 467 mass parts when CM-modified CNF was 100 mass parts) and then placed in a vial and left to stand at room temperature, bubbles were confirmed to remain after 1 week. In summary, by mixing HEC and CM-modified CNF, high initial foaming properties and high bubble stabilization effects over time can be obtained.

[0102] <Example 2>

[0103] A 1.0 mass % aqueous dispersion of the CMized CNF obtained above was prepared. In addition, as a nonionic water-soluble polymer, a 1.0 mass % aqueous dispersion of polyethylene glycol (molecular weight 4000000) (hereinafter, "polyethylene glycol" is abbreviated as "PEG") was prepared. In a 250 ml polypropylene container with a lid (manufactured by AS ONE, trade name: Pack Clean), 100 g of each of the obtained CMized CNF 1.0 mass % aqueous dispersion and PEG 1.0 mass % aqueous dispersion were added in a manner to form the mass ratio described in Table 2. Each sample was stirred at 3000 rpm for 10 minutes using a homogenizer. In order to evaluate the foamability and bubble stability, the height from the bottom surface of the container to the upper surface of the dispersion was measured for samples that had just been stirred and left to stand at room temperature for 10 minutes and samples that had been left to stand for 1 hour. In addition, photographs were taken. The photographs are shown in Figure 2 .

[0104] [Table 2]

[0105]

[0106] according to Figure 2 From the photographs, it can be seen that in the case of only PEG, foaming can be confirmed immediately after stirring, but the foaming gradually disappears after 10 minutes. In contrast, it can be seen that the foaming property and bubble stability of the sample mixed with PEG and CM-modified CNF are improved.

[0107] <Comparative Example 1>

[0108] Prepare a 1.0 mass % aqueous dispersion of the CMized CNF obtained above. In addition, as an anionic water-soluble polymer, a carboxyvinyl polymer (Copyright Iwase Cosfa, trade name Carbopol (registered trademark) 940 Polymer) (hereinafter, "carboxyvinyl polymer" is abbreviated as "carbomer".) A 0.08 mass % aqueous dispersion of carbomer is prepared in a manner to obtain a viscosity equivalent to that of the CMized CNF 1.0 mass % aqueous dispersion. In a 250 ml polypropylene container with a lid (AS ONE, trade name: Pack Clean), 100 g of the CMized CNF 1.0 mass % aqueous dispersion and 0.08 mass % aqueous dispersion of carbomer are added in a manner to obtain a mass ratio as described in Table 3. Each sample is stirred at 3000 rpm for 10 minutes with a homogenizing disperser. For the sample just after stirring, the height from the bottom surface of the container to the upper surface of the dispersion is measured in the same manner as in Examples 1 and 2. In addition, photographs are taken. The photographs are shown in Figure 3 .

[0109] [Table 3]

[0110]

[0111] according to Figure 3 From the photos, it can be seen that no matter whether it is the case of only carbomer or the case of mixing carbomer with CM-modified CNF, there is almost no foaming and the foaming property is low.

[0112] <Comparative Example 2>

[0113] The PEG in Example 2 was replaced with carboxymethyl cellulose (F350HC-4 manufactured by Nippon Paper Industries, Ltd.) as an anionic water-soluble polymer (hereinafter, "carboxymethyl cellulose" is abbreviated as "CMC"). In the same manner as in Example 2, a 1.0% by mass aqueous dispersion of CMized CNF and a 1.0% by mass aqueous dispersion of CMC were mixed in a mass ratio as shown in Table 4 and loaded into a polypropylene container. Each sample was stirred at 3000 rpm for 10 minutes using a homogenizer. For the sample just after stirring, the height from the bottom surface of the container to the upper surface of the dispersion was measured in the same manner as in Examples 1 and 2. In addition, a photograph was taken. The photograph is shown in Figure 4 .

[0114] [Table 4]

[0115]

[0116] according to Figure 4 From the photographs, it can be seen that no matter whether it is the case of CMC alone or the case of CMC mixed with CM-modified CNF, there is almost no foaming and the foaming property is low.

[0117] <Comparative Example 3>

[0118] The PEG in Example 2 was replaced with xanthan gum (KELTROL (registered trademark) CG-T manufactured by Sanjing Co., Ltd.) as an anionic water-soluble polymer. In the same manner as in Example 2, CMized CNF 1.0 mass % aqueous dispersion and xanthan gum 1.0 mass % aqueous dispersion were mixed in a manner to form the mass ratio described in Table 5 and then loaded into a polypropylene container. Each sample was stirred at 3000 rpm for 10 minutes using a homogenizer. For the samples just after stirring and after standing for 1 day, the height from the bottom of the container to the upper surface of the dispersion was measured in the same manner as in Examples 1 and 2. In addition, photographs were taken. The photographs are shown in Figure 5 .

[0119] [Table 5]

[0120]

[0121] according to Figure 5From the photographs, it can be seen that in the case of xanthan gum alone, foaming can be confirmed just after stirring, but the bubbles disappear after 1 day. In addition, it can be seen that for the sample mixed with xanthan gum and CMized CNF, foaming can also be confirmed just after stirring, but no obvious improvement in foamability is found, and the bubbles disappear after 1 day in the same manner as in the case of xanthan gum alone.

[0122] <Example 3>

[0123] 100 g of an aqueous dispersion containing 0.2% by mass of the CMized CNF obtained above and 0.01% by mass of sodium lauryl sulfate was placed in a 600 ml covered polypropylene container (manufactured by AS ONE, trade name: Pack Clean), and stirred at 3000 rpm for 5 minutes using a homogenizer. As a comparison, an aqueous dispersion containing only 0.01% by mass of sodium lauryl sulfate was also placed in the container and stirred. In order to evaluate the foamability and bubble stability, the height from the bottom of the container to the upper surface of the dispersion was measured for samples just after stirring, after standing at room temperature for 5 minutes, and after standing for 10 minutes. In addition, photographs were taken. The photographs are shown in Figure 6 .

[0124] according to Figure 6 , it can be seen that in the case of sodium lauryl sulfate alone, separation of the foam layer and the liquid phase was observed immediately after stirring. On the other hand, it can be seen that the foaming property of the sample mixed with sodium lauryl sulfate and CM-modified CNF was improved immediately after stirring, and the bubble stability over time was also improved.

[0125] <Example 4>

[0126] A 1.0 mass % aqueous dispersion of the CMized CNF obtained above was prepared. In addition, as a nonionic water-soluble polymer, a 1.0 mass % aqueous dispersion of methyl cellulose (Methyl Cellulose (7000-10000 mPa·s, 2% in Water at 20°C), Tokyo Chemical Industry Co., Ltd.) (hereinafter, "methyl cellulose" is abbreviated as "MC") was prepared. In a 250 ml polypropylene container with a lid (manufactured by AS ONE, trade name: Pack Clean), 100 g of each of the obtained CMized CNF 1.0 mass % aqueous dispersion and MC 1.0 mass % aqueous dispersion were added in a manner to achieve the mass ratio described in Table 6. Each sample was stirred at 3000 rpm for 5 minutes using a homogenizer. In order to evaluate the foamability and bubble stability, the height from the bottom surface of the container to the upper surface of the dispersion was measured for samples that had just been stirred and left to stand at room temperature for 10 minutes, samples that had been left to stand at room temperature for 1 day, and samples that had been left to stand at room temperature for 4 days. In addition, photographs were taken. The photographs are shown in Figure 7 .

[0127] [Table 6]

[0128]

[0129] according to Figure 7 From the photos, it can be seen that in the case of only MC, foaming can be confirmed just after stirring, but the bubbles formed almost disappear after standing for 1 day. On the other hand, it can be seen that in the case of only CM-converted CNF, the foaming property just after stirring is low. In contrast, it can be seen that the foaming property and bubble stability of the sample mixed with MC and CM-converted CNF are improved.

[0130] <Example 5>

[0131] 100 g of an aqueous dispersion containing 0.2% by mass of the CMized CNF obtained above and 0.01% by mass of lauramide propyl hydroxysulfobetaine (Kawaken Fine Chemicals Co., Ltd., trade name: SOFTAZOLINE (registered trademark) LSB-R) was placed in a 600 ml covered polypropylene container (manufactured by AS ONE, trade name: Pack Clean), and stirred at 3000 rpm for 5 minutes using a homogenizer. For comparison, an aqueous dispersion containing only 0.01% by mass of lauramide propyl hydroxysulfobetaine was also placed in a container and stirred. In order to evaluate the foamability and bubble stability, the height from the bottom surface of the container to the upper surface of the dispersion and the height from the bottom surface of the container to the lower surface of the bubbles were measured for samples immediately after stirring, after standing at room temperature for 5 minutes, and after standing for 10 minutes. In addition, photographs were taken. The photographs are shown in Figure 8 .

[0132] according to Figure 8 , it can be seen that in the case of lauramide propyl hydroxysulfobetaine alone, foaming is small and the bubble stability is low. On the other hand, it can be seen that the sample in which lauramide propyl hydroxysulfobetaine is mixed with CM-modified CNF has improved foaming properties immediately after stirring and improved bubble stability over time.

[0133] <Example 6>

[0134] The foamability and bubble stability were evaluated in the same manner as in Example 5 except that 0.01% by mass of lauramidopropyl hydroxysulfobetaine was replaced with 0.2% by mass of decyl dimethylamine oxide (LION SPECIALTY CHEMICALS Co., Ltd., trade name: CADENAX (registered trademark) DM10D-W). Fig. 9 .

[0135] according to Fig. 9, it can be seen that there is no foaming in the case of decyl dimethyl amine oxide alone. On the other hand, it can be seen that foaming occurs by mixing decyl dimethyl amine oxide with CM-modified CNF, and the bubble stability is also good.

[0136] <Example 7>

[0137] The foamability and bubble stability were evaluated in the same manner as in Example 5 except that 0.01% by mass of lauryl amine oxide (LION SPECIALTY CHEMICALS Co., Ltd., trade name: CADENAX (registered trademark) DW12D-W (C)) was changed to 0.003% by mass of lauryl amine oxide. Fig.10 .

[0138] according to Fig.10 From the photographs of FIG. 1 , it can be seen that when lauramine oxide is mixed with CM-conjugated CNF, the height from the lower surface of the container to the bottom of the bubble is not easy to increase over time compared to the case of only lauramine oxide. This means that the dispersion that has become bubbles is not easy to return to a liquid state, which shows that the bubble stability is improved by mixing lauramine oxide with CM-conjugated CNF. In addition, compared to the case of only lauramine oxide, when lauramine oxide is mixed with CM-conjugated CNF, it can be observed that the bubbles become finer.

[0139] <Example 8>

[0140] The foamability and bubble stability were evaluated in the same manner as in Example 5 except that 0.01% by mass of lauramide propyl hydroxysulfobetaine was changed to 0.03% by mass of sodium oleate. Fig.11 .

[0141] according to Fig.11 From the photos, it can be seen that when sodium oleate is mixed with CM-CNF, the height from the lower surface of the container to the bottom of the bubble is not easy to increase over time compared with the case of only sodium oleate. This means that the dispersion that has become bubbles is not easy to return to a liquid state, which shows that the stability of bubbles is improved by mixing sodium oleate with CM-CNF. In addition, compared with the case of only sodium oleate, when sodium oleate is mixed with CM-CNF, it can be observed that the bubbles become delicate.

Claims

1. An additive for producing a bubble-containing composition, comprising: carboxymethylated cellulose nanofibers, and a nonionic water-soluble polymer, wherein the carboxymethylated cellulose nanofibers have a degree of substitution of carboxymethyl groups per glucose unit of 0.01 to 0.50, a cellulose I type crystallinity of 40% or more, and a fiber width of 4 to 500 nm, The nonionic water-soluble polymer is at least one selected from hydroxyethyl cellulose, hydroxypropyl methyl cellulose, or hydroxyethyl methyl cellulose.

2. The additive for producing a bubble-containing composition according to claim 1, wherein The nonionic water-soluble polymer is hydroxyethyl cellulose.

3. The additive for producing a bubble-containing composition according to claim 1, wherein The amount of the nonionic water-soluble polymer is 1 to 5000 parts by mass based on 100 parts by mass of the carboxymethylated cellulose nanofibers. 4 . A method for producing a bubble-containing composition, comprising mixing the additive for producing a bubble-containing composition according to claim 1 into a material for a bubble-containing composition and stirring the material to foam the material.

5. A method for stabilizing bubbles in a bubble-containing composition, comprising adding the additive for producing a bubble-containing composition according to any one of claims 1 to 3 to the bubble-containing composition.

Citation Information

Patent Citations

  • Stabilizer for ice cream and method for producing ice cream

    JP2005143321A

  • Liquid egg composition and egg processed food

    JP2009065836A

  • Composite of fiber and inorganic particles

    CN110023558A

  • Additive for bubble-containing composition

    JP2008238115A

  • Additive for air bubble containing composition

    JP2017066283A